Finding extrema without resorting to calculus - Victor Oxman; Moshe Stupel; Jay M. Jahangiri (Cogent Education, 2018)
The article is dedicated to solving extrema problems in teaching mathematics, without using calculus. We present and discuss a wide variety of mathematical extrema tasks where the extrema are obtained and find their solutions without resorting to differential. Particular attention is paid to the role of arithmetic and geometric means inequality in solving these problems.